Menakar Penerapan Standar Operasional Prosedur Budidaya Untuk Pengendalian Kualitas Hasil Panen Jagung - Achmad Ivan Dwi Putra; Moh Agung Surianto (Universitas Pendidikan Nasional, 2021)
This research was conducted at PT. Agro Aku Bisa Jember, East Java. The aims of this study were (1) to analyze the application of standard operating procedures for cultivation on maize farming at PT. Agro Aku Bisa Jember; (2) the effectiveness of the implementation of Quality Control of maize yields at PT. Agro Aku Bisa Jember. The basic method used is descriptive qualitative with case study implementation method. Data were collected by interview, observation and documentation methods. The results showed that the application of standard cultivation procedures had been carried out well in the process of planting to harvesting based on the principles, namely: (a) pre-planting land maintenance process (b) periodic maintenance of corn plants.